Analisis Potensi, Efektivitas dan Kontribusi Pajak Restoran Kecamatan Kuta Utara pada Pendapatan Asli Daerah Kabupaten Badung - Dewi, Ni Luh Risma Andika; Dwi Ratnadi, Ni Made (E-Jurnal Akuntansi; Vol 31 No 2 (2021), 2021)
The purpose of this study was to determine the restaurant tax potential, the effectiveness of restaurant tax collection, and the contribution of restaurant tax North Kuta District to Local Revenue in the of Badung Regency. This research was conducted at restaurants in the North Kuta District totaling 185 taxpayers in 2019. The analysis technique used was a quantitative descriptive analysis that could calculate the potential value, effectiveness of collection, and restaurant tax contributions in the North Kuta District. The results of the analysis show the restaurant tax potential in the North Kuta District in 2019 amounted to 212.7 percent of the realization of the restaurant tax in the North Kuta District in 2018. The effectiveness of restaurant tax collection in the North Kuta District based on the potential restaurant tax in 2019 amounted to 47.01 percent which includes the criteria ineffective. Restaurant tax in North Kuta Subdistrict contributed 0.84 percent to the total Badung Regency Revenue in 2018. Keywords: Restaurant Tax; Effectiveness; Potency; Contribution.